บรรยากาศองค์กรที่ส่งผลต่อการจัดประสบการณ์สำหรับเด็กปฐมวัย สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสมุทรสาคร - พูลจักร์, เพลินตา (วารสาร ศึกษาศาสตร์ มมร, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาบรรยากาศองค์กร การจัดประสบการณ์สำหรับเด็กปฐมวัย และบรรยากาศองค์กรที่ส่งผลต่อการจัดประสบการณ์สำหรับเด็กปฐมวัย สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสมุทรสาคร ประชากร คือ โรงเรียน 104 โรงเรียน ได้กลุ่มตัวอย่าง จำนวน 86 โรงเรียน ผู้ให้ข้อมูลทั้งสิ้น 344 คน ประกอบด้วย ผู้บริหาร/รองผู้บริหารสถานศึกษา หัวหน้าสายชั้น และครู เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถาม วิเคราะห์ข้อมูลโดยใช้โปรแกรมสำเร็จรูปในการวิเคราะห์ค่าสถิติพื้นฐาน ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์การถดถอยพหุคูณ แบบขั้นตอน  ผลการวิจัยพบว่า 1. บรรยากาศองค์กร โดยภาพรวมอยู่ในระดับมาก โดยเรียงลำดับจากมากไปหาน้อย ดังนี้ การผนึกกำลังเหนียวแน่น การดูแลเอาใจใส่ การยอมรับนับถือ และการมีขวัญสูง เท่ากับโอกาสในการทำงาน ตามลำดับ 2. การจัดประสบการณ์สำหรับเด็กปฐมวัย โดยเรียงลำดับจากมากไปหาน้อย ดังนี้ พัฒนาการด้านร่างกาย พัฒนาการด้านอารมณ์และจิตใจ พัฒนาการด้านสติปัญญา และพัฒนาการด้านสังคม ตามลำดับ 3. บรรยากาศองค์กรที่ส่งผลต่อการจัดประสบการณ์สำหรับเด็กปฐมวัย อย่างมีนัยสำคัญทางสถิติที่ระดับ .01 ABSTRACT The objective of the research was to study the motivation of performancesof the teachers in the schools under the jurisdiction, the quality of early childhood , and the motivation of performancesof the teachers affecting the quality of early childhood of the Office of SamutSakhon Primary Educational Service Area. The population comprised 104 primary schools attached to the Office of SamutSakhon Primary Educational Service Area, of which 86 schools were selected as samples, with the school directors/deputy directors, program chiefs and teachers as informants numbering 344 in total. The tool used for data collection was a questionnaire. The computer program wasemployed for data analysis, with the statistical devices, namely, frequency, percentage, mean and stepwise multiple regression analysis. The results of the study were as follows: 1. The motivation of performances was found, in an overall aspect, to remain at a ‘Much’ level. In an individual aspect, the item that was found to be the top rank was the relationship of the teachers, followed by job satisfaction, premises and service, workloads and the neighboring communities’ supports, respectively. 2. The quality of early childhood was found inclusively to stand at a ‘Much’ level. Exclusively, the item that stood on top of the scale was intellectual development, followed by social, physical and emotional and mental developments, respectively. 3. The motivation of performancesof the teachers affecting the quality of early childhood as mentionedwas found todisplay the statistical significance at.01.